(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the study of enigmatic texts as an object of linguistic research. The setypesoftextsaimed at revealing enigmat are distinguished by their specific ways of usage. In the enigmatic texts, the descriptive aids and connotative structure aimed at identifying denotations, which are also the point of discussions.